(Im) Possibilidades da implementação da terminalidade específica na educação superior - Silva, Mariane Carloto da (2022)
This Doctoral thesis in Education is linked to the line of research Special Education, Inclusion, and Difference of the Graduate Program in Education at the Federal University of Santa Maria (UFSM). This study discusses the institutionalization of Specific Terminality Certification in Higher Education. The general objective of this research was to understand the practices and consequences of the applicability of Specific Terminality, analyzing its possibilities for the professional training of students who are the target audience of Special Education in undergraduate programs. Thus, we defend that there are certain types of disability whose impairment can affect the learning of curricular skills, making Specific Terminality Certification appropriate. This research is qualitative, exploratory, and analytical, and it was developed from data collected in institutional documents of eleven Federal Institutes of Education, Science, and Technology. These documents deal with Specific Terminality Certification; a semi-structured open interview with twelve Pro-Rectors (eleven Pro-Rectors of Education from Federal Institutes and one Pro-Rector of Undergraduate program from a Federal University), and an open questionnaire with three graduates certified by Specific Terminality. Data were analyzed using Content Analysis of the Categorical type proposed by Bardin (2011). The systematization of the collected data showed that Specific Terminality transcends certification. This is due to the fact that it is linked to the process of academic monitoring and curricular accessibility, the appreciation of the subject, and the acquisition of autonomy and social belonging. Results show that the practices and contributions of Specific Terminality aim to enable an academic certification and guidance for professional practice provided that the student's conditions are adequate after a process of curricular accessibility that will allow students to complete the degree. The negative aspects are concerning the inappropriate use of Specific Terminality Certification (there is a team of professionals facing this demand to prevent this) and the social and professional recognition of the diploma without a legal basis for its non-acceptance. There might be evidence that Specific Terminality may become a University Institutional Policy, taking advantage of its institutional autonomy, legal support, and what already exists in Federal Education Institutions. In conclusion, implementing the Specific Terminality Certification in Higher Education, based on the current legal documentation, is possible since it is necessary to implement actions that allow the permanence, learning, and completion in Higher Education for students target audience.